Histamine is stored in mast cells of most evolutionarily advanced fish and regulates the fish inflammatory response - Mulero, Iván (National Academy of Sciences, 2007)
Mast cells are important as initiators and effectors of innate immunity and regulate the adaptive immune responses. They have been described in all classes of vertebrates and seem to be morphologically and functionally similar. However, early studies had shown that fish and amphibian mast cells were devoid of histamine. In this study, we take a fresh look at the evolution of histamine and find that the mast cells of fish belonging to the Perciformes order, the largest and most evolutionarily advanced order of teleosts, are armed with histamine. More importantly, histamine is biologically active in these fish where it is able to regulate the inflammatory response by acting on professional phagocytes. In addition, the actions of histamine in these immune cells seem to be mediated through the engagement of H(1) and H(2) receptors, which, together with the H(3) receptor, are well conserved in bony fish. We propose that the storage of histamine in vertebrate mast cells and its use as an inflammatory messenger was established in primitive reptiles (Lepidosauria) ≈276 million years ago. This same feature seems to have developed independently in Perciform fish much more recently in the Lower Eocene, between 55 and 45 million years ago, a short period during which the great majority of Percomorph families appeared.